2024
DOI: 10.1002/cncr.35210
|View full text |Cite
|
Sign up to set email alerts
|

Does hormone therapy impact cognition in patients with prostate cancer? A systematic review and meta‐analysis

Antoine Boué,
Florence Joly,
Justine Lequesne
et al.

Abstract: BackgroundHormone therapy, which is widely prescribed for prostate cancer, might induce cognitive impairment and affect the autonomy of elderly patients. However, previous studies provided conflicting results. The aim of this systematic review and meta‐analysis was to synthesize the longitudinal impact of hormone therapy on objective (cognitive tests) and subjective (questionnaires) cognition.MethodsA search was performed of the PubMed, Web of Science, and PsycINFO databases. Studies that longitudinally assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…meta-analysis by Boué et al in this issue of Cancer is the latest and most robust synthesis of the literature thus far, with the inclusion of both ADT and ARAT studies and an analysis of cognitive effects by specific cognitive domains. 4 Previous systematic reviews and meta-analyses produced inconsistent results, and most omitted the newer ARATs in favor of ADTs only. In 2015, McGinty et al's meta-analysis of 14 studies found that patients treated with ADT performed worse than controls or their own baseline on visuomotor tasks, although none of the other six cognitive domains showed significant changes.…”
mentioning
confidence: 99%
“…meta-analysis by Boué et al in this issue of Cancer is the latest and most robust synthesis of the literature thus far, with the inclusion of both ADT and ARAT studies and an analysis of cognitive effects by specific cognitive domains. 4 Previous systematic reviews and meta-analyses produced inconsistent results, and most omitted the newer ARATs in favor of ADTs only. In 2015, McGinty et al's meta-analysis of 14 studies found that patients treated with ADT performed worse than controls or their own baseline on visuomotor tasks, although none of the other six cognitive domains showed significant changes.…”
mentioning
confidence: 99%